A patient with non-mosaic 47, XXY karyotype fathering a normal healthy infant using intracytoplasmic sperm injection (ICSI) - a case report - H. Ye; S. Xue1; Y. Kuang; L. Sun (IMR Press, 2020)
Background: Klinefelter's Syndrome (KS) is rarely reported in China, which is associated with insufficient sperm production and infertility in male patients. Despite the fact that infertility treatments, such as intracytoplasmic sperm injection (ICSI) and preimplantation genetic diagnosis (PGD), have been widely used in KS population, almost all these patients have to use donor semen in China to establish successful pregnancies nowadays. Case Report: The authors report a case of KS in a patient with unremarkable characteristics except for oligospermia. The patient presented to this center with infertility and the chromosome analysis demonstrated a non-mosaic 47, XXY karyotype. Further testing showed no deletions in the SRY, AZF-a, AZF-b, and AZF-c genes. Finally, the patient successfully impregnated the partner, and then the partner delivered a healthy male neonate. The patient became fertile through ICSI, together with cryopreservation of a small number of spermatozoa after the first blastocyst transfer. Conclusion: This report further confirms that KS men can father their own healthy children. While adequate sperm cryopreservation and blastocyst transfers are strongly recommended. Nevertheless, it is necessary for such couples to be offered extensive genetic counseling before pregnancy and prenatally.